The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.2.12118/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Older adults' preferences for, adherence to and experiences of two self-management falls prevention home exercise programmes: A comparison between a digital programme and a paper booklet

Abstract: Background: Fall prevention exercise programmes are known to be effective, but access to these programmes is not always possible. The use of eHealth solutions might be a way forward to increase access and reach a wider population. In this feasibility study the aim was to explore the choice of programme, adherence, and self-reported experiences comparing two exercise programmes – a digital programme and a paper booklet.Methods: A participant preference trial of two self-managed fall prevention exercise interven… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…31 Additional strategies are therefore needed to attract older adults who are less prone to using digital technology for health purposes. In a previous study, we found that a proportion of people did not wish to use digital technology and instead used paper-based resources, 32 but it is likely that more regular prompting to support behaviour change and regularity of use may be necessary as compliance to the exercise prescription was better when prompted by the digital technology. 32 Although eHealth literacy is negatively associated with age, 28 and older adults are more often represented among non-users of the Internet, 18 this group is rapidly decreasing, and older adults are becoming more accustomed to using smartphones and tablets.…”
Section: Discussionmentioning
confidence: 92%
“…31 Additional strategies are therefore needed to attract older adults who are less prone to using digital technology for health purposes. In a previous study, we found that a proportion of people did not wish to use digital technology and instead used paper-based resources, 32 but it is likely that more regular prompting to support behaviour change and regularity of use may be necessary as compliance to the exercise prescription was better when prompted by the digital technology. 32 Although eHealth literacy is negatively associated with age, 28 and older adults are more often represented among non-users of the Internet, 18 this group is rapidly decreasing, and older adults are becoming more accustomed to using smartphones and tablets.…”
Section: Discussionmentioning
confidence: 92%
“…The OTAGO exercise program (OEP) it is a well described falls program, flexible in its implementation, which can be either home or community based. It consists of warm up and cool down phase, strengthening balance and gait exercises as the main pillars of the program, and can be performed either on a group or in personal [63][64][65]. It is a well-documented and structured tool, disseminated widely to the physiotherapy community as it offers a significant reduction of morbidity and mortality and falls for the participants in a one-year prevalence time [66].…”
Section: Balance Disordersmentioning
confidence: 99%
“…22 The majority of the participants exercised at least during 75% of the intervention weeks and one-third of the participants completed more than 75% of recommended exercise time. 29 To investigate the effectiveness of a self-managed digital exercise programme, this randomised (1:1) controlled trial (RCT) aims to compare the Safe Step application in combination with monthly educational videos with a control group that only receives the educational videos.…”
Section: Open Accessmentioning
confidence: 99%